ASSESSMENT OF THE STATE OF DEVELOPMENT OF STRATEGIES FOR SOCIO-ECONOMIC DEVELOPMENT OF UTC - Sologub , S.I. (The actual problems of regional economy development, 2022)
The article is aimed at studying the assessment of the state of development of strategies for socio-economic development of UTC in the context of decentralization reform. The actualization of the need for research is primarily due to the fact that among scientists there is no single position on the evaluation of strategy development, and more attention is focused on the process of implementing the strategy, which requires more in-depth research. Therefore, this study aims to assess the state of development of TC development strategies on the example of Kalush district on the basis of comparative and content analysis to identify the real state of development of socio-economic development strategies of local communities in the implementation of decentralization reform. The assessment of the state of community strategies was carried out on the example of Kalush district of Ivano-Frankivsk region, which includes 13 territorial communities with 162 settlements. As a percentage of the results of the study of the state of development of strategies for socio-economic development of communities of Kalush district we have the following situation: 54% of local communities have developed a strategy, 23% - strategies under development, and 23% of communities do not have a strategy. If we determine the reasons for this situation, the relationship between the date of UTC and the state of strategy development is not fully supported. The assessment of strategies in terms of the state of development was focused on assessing the formation of strategic vision and goals, compliance with regulations governing the development of the region, as well as the availability of certain features and additional tools to successfully implement the strategy. It was also found that not all communities have a strategy as a comprehensive document, which reflects the long-term vision of socio-economic development of the community, and especially not all can find the prerequisites to increase investment attractiveness of united territorial communities. Given the limited resources and challenges, it is an important factor in ensuring the existence and sustainable development of the community on the basis of increasing their investment attractiveness.